Fitness Wearables and Youths with Visual Impairments: Implications for Practice and Application. (September 2016) - Colgan, Joanna C.; Bopp, Melissa J.; Starkoff, Brooke E.; Lieberman, Lauren J.
Introduction: Individuals with visual impairments are at risk for chronic health-related illnesses attributed to low physical activity and low fitness levels. This study aimed to determine device preference of three physical activity–monitoring wearables for youths with visual impairments, taking into account gender and visual impairment level, and to discern beneficial and impeding device components and suggested device changes. Methods: For this cross-sectional and descriptive study, a convenience sample of 25 youths and young adult volunteers (16 males, 9 females, aged 9–22, M = 13.80, SD = 3.27) were recruited from a week-long sports camp for youths with visual impairments. Participants were assigned to wear all three wearables at once. Data was collected through demographic questionnaires and evening focus groups and was analyzed using qualitative coding software to determine beneficial and impeding aspects and suggested device changes. Results: Responses varied by level of visual impairment, such as with auditory and visual contrast components, and varied slightly by gender, such as with aesthetic components. All responses for beneficial and impeding components and suggested changes fell into coded themes of access to data, comfort, display, data measured, auditory, waterproof, aesthetics, goal-setting, and music. Discussion: Beneficial and impeding components helped participants suggest changes to make devices more usable, accessible, easy and enjoyable to wear, and motivating for this population. Limitations include the short device usage time for each participant, financial constraints, and the number of participants who consented. Implications for practitioners: Physical activity technology can be developed that is more usable by more members of the general population and that allows more individuals to meet daily and weekly physical activity recommendations and health goals. In terms of reducing health disparities, this technology can mass-target physical activity levels in individuals with visual impairments as part of low-cost health and physical activity promotion interventions and could increase the overall quality of life of at-risk individuals.